Variant origin of common hepatic and middle colic artery- a case report. - Samanta PP; Kharb P; Atulya (Penerbit UKM, 2013)
Variation of common hepatic or middle colic artery may account for the complications which arise during liver transplantation and surgeries of upper abdomen. We here report a case of an anomalous branching pattern of ventral branches of abdominal aorta in a 50-year-old male cadaver. The coeliac trunk originated from the ventral aspect of abdominal aorta and bifurcated into left gastric and splenic arteries. The common hepatic artery originated directly from the abdominal aorta, 0.2cm inferior to the origin of coeliac trunk. The middle colic artery originated from the proximal segment of splenic artery instead of its usual origin, the superior mesenteric artery. A separate middle colic branch of superior mesenteric artery was not observed. Anatomical variations in the branching patterns of coeliac trunk and superior mesenteric arteries are not infrequent. However, the concomitant variant origins of branches of coeliac trunk and middle colic artery is a rare anomaly and its knowledge would therefore be helpful in operative procedures of abdomen and image guided interventions.